Should data from demographic surveillance systems be made more widely available to researchers? - Daniel Chandramohan; Kenji Shibuya; Philip Setel; Sandy Cairncross; Alan D Lopez; Christopher J L Murray; Basia Zaba; Robert W Snow; Fred Binka (PLoS Medicine)
Background to the debate Demographic surveillance--the process of monitoring births, deaths, causes of deaths, and migration in a population over time--is one of the cornerstones of public health research, particularly in investigating and tackling health disparities. An international network of demographic surveillance systems (DSS) now operates, mostly in sub-Saharan Africa and Asia. Thirty-eight DSS sites are coordinated by the International Network for the Continuous Demographic Evaluation of Populations and Their Health (INDEPTH). In this debate, Daniel Chandramohan and colleagues argue that DSS data in the INDEPTH database should be made available to all researchers worldwide, not just to those within the INDEPTH Network. Basia Zaba and colleagues argue that the major obstacles to DSS sites sharing data are technical, managerial, and financial rather than proprietorial concerns about analysis and publication. This debate is further discussed in this month's Editorial.